Using a genre-based approach to promote oral communication in the colombian english classroom - Herazo Rivera, Jose David (Colombian Applied Linguistics Journal, 2012)
The genre-based approach (GBA) has been used in different curriculum areas to develop learners’ meaning-making potential. Using the text as the main unit of communication and pedagogy, this approach conceives of language learning and use as a social, textual, and goaloriented process. Thus, it constitutes a promising alternative to the practice –not uncommon in Colombian classrooms– of teaching EFL oral communication through memorized dialogues with no realistic purpose. Based on a revision of recent literature and research, I argue that the GBA may foster students’ oral interpersonal communication skills because it 1) involves them in meaning-oriented, text-based, and realistic practice, 2) assumes an explicit pedagogy that discloses the lexical and grammatical resources needed for successful communication, and 3) facilitates learners’ increasing control of oral communication thanks to their appropriation of the necessary metalanguage to talk about the process of making meaning in English. I also maintain that this approach gives teachers linguistically-principled tools for planning instruction and assessing learning. Finally, I discuss various curriculum and syllabus implications resulting from the adoption of the GBA for EFL instruction and suggest specific objectives and activities with a sample lesson based on Colombian standards.